2020
DOI: 10.1002/ccd.28708
|View full text |Cite
|
Sign up to set email alerts
|

Northwell intracoronary brachytherapy for the treatment of recurrent drug eluting stent in‐stent restenosis (NITDI study group)

Abstract: Objective: The purpose of this study is to report on safety, short-term and long-term clinical efficacy following intracoronary brachytherapy (ICBT) for restenosis (ISR) in patients with drug eluting stents (DES). Background: ICBT is an effective treatment for ISR of bare metal stents (BMS) but its utilization has waned due to the advent of DES. ISR following DES occurs at a frequency of 8% or greater. Method: A retrospective analysis was performed on patients treated on an institutional review board (IRB) app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
(44 reference statements)
0
10
0
Order By: Relevance
“…Multiple studies have demonstrated lower rates of MACE with VBT compared to re-DES for DES-ISR (Table 4, Ref. [18,22,35,80,[82][83][84][85][86], Supplementary Table 1), Fig. 3.…”
Section: Efficacy 431 Major Adverse Cardiac Events (Mace)mentioning
confidence: 98%
See 3 more Smart Citations
“…Multiple studies have demonstrated lower rates of MACE with VBT compared to re-DES for DES-ISR (Table 4, Ref. [18,22,35,80,[82][83][84][85][86], Supplementary Table 1), Fig. 3.…”
Section: Efficacy 431 Major Adverse Cardiac Events (Mace)mentioning
confidence: 98%
“…The patients in this study either had VBT for DES-ISR initially or presented with symptoms including angina requiring VBT (Table 1, Ref. [18,22,35,80,[82][83][84][85]). The patients presenting with ST segment elevation myocardial infarction (STEMI), cardiogenic shock or angiographic stent thrombosis were excluded from some of the studies (Table 1).…”
Section: Patient Demographic and Baseline Clinical Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…While stenting within a restenosis is ubiquitous, stenting when there are already two layers of stents is generally disapproved of. Beta radiation, with the Novoste Beta‐cath system, once again appears to be an excellent option in these complicated and previously treated lesions 4 . While drug eluting balloons show promising results in the treatment of in‐stent restenosis they are currently not widely available in the United States.…”
mentioning
confidence: 99%